Оцінка життєздатності природних популяцій Pinus sylvestris L. Кременецького горбогір’я та Малого Полісся за мінливістю кількісних та якісних ознак - Lisnichuk, A.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The vital capacity of three natural populations of Pinus sylvestris L. of Kremenets hillocks and Small Polissia by vitality, age structure, density and number seed productivity, relation of the components of allele diversity inside and outside populations is investigated. It is found that the observed population is characterized by a high level of genetic variability and great stable vital capacity.